The Charter of the City of Newport, R. I., and the Special State Laws Relating Thereto, Together with the Ordinances for the Government of the City, at 39, An Act providing in case of fire breaking out in the town of Newport an for the purposes therein mentioned, § 12 (1858) - (:unkn) unknown (General Publisher, 1858)
Prohibited ships with more than 5 barrels of gunpowder on board from entering the harbor
--
Keywords: GUN POWDER TRANSPORTATION